CATHODOLUMINESCENCE (CL) AND ELECTRON PARAMAGNETIC RESONANCE (EPR) STUDIES OF CLAY MINERALS - Gotze J.; Plotze M.; Gotte Th.; Neuser R.D.; Richter D.K. (My University, 2002)
Sheet silicates of the serpentine-kaolin-group (serpentine, kaolinite, dickite, nacrite, halloysite), the talc-pyrophyllite-group (talc, pyrophyllite), the smectite-group (montmorillonite), and illite (as a mineral of the mica-group) were investigated to obtain information concerning their cathodoluminescence behaviour. The study included analyses by cathodoluminescence (CL microscopy and spectroscopy), electron paramagnetic resonance (EPR), X-Ray diffraction (XRD), scanning electron microscopy (SEM) and trace element analysis. In general, all dioctahedral clay minerals exhibit a visible CL. Kaolinite, dickite, nacrite and pyrophyllite have a characteristic deep blue CL, whereas halloysite emission is in the greenish-blue region. On the contrary, the trioctahedral minerals (serpentine, talc) and illite do not show visible CL. The characteristic blue CL is caused by an intense emission band around 400 nm (double peak with two maxima at 375 and 410 nm). EPR measurements indicate that this blue emission can be related to radiation induced defect centres (RID), which occur as electron holes trapped on apical oxygens (Si-O centre) or located at the Al-O-Al group (Al substituting Si in the tetrahedron). Additional CL emission bands were detected at 580 nm in halloysite and kaolinite, and between 700 and 800 nm in kaolinite, dickite, nacrite and pyrophyllite. Time-resolved spectral CL measurements show typical luminescence kinetics for the different clay minerals, which enable differentiation between the various dioctahedral minerals (e.g. kaolinite and dickite), even in thin section.